2012
DOI: 10.2741/s262
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specificities of tumor induction by aromatic amines

Abstract: Introduction 3. What is required for the induction of tumors by chemicals? 3.1. Modification of protein by AA 3.2. Modification of nucleic acids by AA 3.3. Reactive nitrenium derivatives 3.3.1. Formation by cytosolic acyltransferases 3.3.2. Formation by microsomal acyltransferases 3.3.3. Formation by cytosolic sulfotransferase 3.3.4. Circumventing the need for enzymatic N-oxidation 3.4. Activation by cyclooxygenases 3.5. What are the criteria for the production of tumors in humans by AA? 3.5.1. Distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The NADPHcytochrome P-450, various forms of P-450, and peroxidase such as bladder prostaglandin H synthase (PHS) can also activate aromatic amines to reactive free radical intermediates or produce reactive oxygen species (ROS). Review of mechanisms of carcinogenic processes of these aromatic amines is available elsewhere and will not be repeated here [42][43][44][45]. The International Agency for Research on Cancer (IARC) evaluated some aromatic amines, organic dyes, and related exposure in Leon, France, in 2008 and concluded that benzidine (Bz), dyes metabolized to Bz, auramine production, magenta production, 4,4'-methylenebis(2-choroaniline) (MOCA), 4-ABP, NA, and o-toluidine as group 1 carcinogens (the agent is carcinogenic to humans), 4-chloro-o-toluidine, and occupational exposure to hair dyesasa hairdresser as group 2Acarcinogens (the agent is probably carcinogenic to humans), and 4-chloro-ortho-toluidine and auramine as group 2B carcinogens(the agent is possibly carcinogenic to humans) [10].…”
Section: Chemicals Referencesmentioning
confidence: 99%
“…The NADPHcytochrome P-450, various forms of P-450, and peroxidase such as bladder prostaglandin H synthase (PHS) can also activate aromatic amines to reactive free radical intermediates or produce reactive oxygen species (ROS). Review of mechanisms of carcinogenic processes of these aromatic amines is available elsewhere and will not be repeated here [42][43][44][45]. The International Agency for Research on Cancer (IARC) evaluated some aromatic amines, organic dyes, and related exposure in Leon, France, in 2008 and concluded that benzidine (Bz), dyes metabolized to Bz, auramine production, magenta production, 4,4'-methylenebis(2-choroaniline) (MOCA), 4-ABP, NA, and o-toluidine as group 1 carcinogens (the agent is carcinogenic to humans), 4-chloro-o-toluidine, and occupational exposure to hair dyesasa hairdresser as group 2Acarcinogens (the agent is probably carcinogenic to humans), and 4-chloro-ortho-toluidine and auramine as group 2B carcinogens(the agent is possibly carcinogenic to humans) [10].…”
Section: Chemicals Referencesmentioning
confidence: 99%